2018
DOI: 10.1002/tcr.201800029
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts Based on Earth‐Abundant Metals for Visible Light‐Driven Water Oxidation Reaction

Abstract: Exploration of water oxidation catalyst (WOC) with excellent performance is the key for the overall water splitting reaction, which is a feasible strategy to convert solar energy to chemical energy. Although some compounds composed of noble metals, mainly Ru and Ir, have been reported to catalyze water oxidation with high efficiency, catalysts based on low-cost and earth-abundant transition metals are essential for realizing economical and large-scale light-driven water splitting. Various WOCs containing earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 156 publications
1
14
0
Order By: Relevance
“…48,52 In the case of Ni-and Cu-based mononuclear WOCs, there was no clearly resolved spectroscopic signal available for either the Ni IV or Cu IV -oxo intermediate species, respectively. 1,53,54 Second, we notice that the reaction mechanism of these first-row TM-based mononuclear WOCs is predominantly proposed as water nucleophilic attack (WNA) to the above discussed high-valent metal-oxo species or metal-oxyl radicals, where O-O bonds are formed. 52,[55][56][57] In this case, first-order reaction kinetics is normally observed for the mononuclear WOCs, 58 which means that the rate-determining step (RDS) involves only one metal center.…”
Section: Recent Progress In Designing Molecular Wocsmentioning
confidence: 99%
“…48,52 In the case of Ni-and Cu-based mononuclear WOCs, there was no clearly resolved spectroscopic signal available for either the Ni IV or Cu IV -oxo intermediate species, respectively. 1,53,54 Second, we notice that the reaction mechanism of these first-row TM-based mononuclear WOCs is predominantly proposed as water nucleophilic attack (WNA) to the above discussed high-valent metal-oxo species or metal-oxyl radicals, where O-O bonds are formed. 52,[55][56][57] In this case, first-order reaction kinetics is normally observed for the mononuclear WOCs, 58 which means that the rate-determining step (RDS) involves only one metal center.…”
Section: Recent Progress In Designing Molecular Wocsmentioning
confidence: 99%
“…These TON and TOF max values of Co 2 DNCH for O 2 evolution in water/acetone-d 6 are relatively high compared to those of CoPF 5 (TOF max = 0.53 s −1 and TON = 164) and other previously reported MWOCs under photochemical conditions. 7,8 To the best of our knowledge, the TON of Co 2 DNCH in this study is the highest among the Co-based MWOC using the photochemical system. The high conversion ratio of the sacrificial reagents for O 2 evolution (over 90%) is still rare in the previous study of MWOC.…”
mentioning
confidence: 67%
“…Polyoxometalates (POMs) as soluble anionic metal oxide clusters of d-block transition metals in high oxidation states, typically W(VI), Mo(V,VI) or V(IV,V), exhibit redox and acid-base properties and are particularly exploited in catalysis, either in homogeneous conditions 1,2 or immobilized in solid supports. [3][4][5][6] In the hot field of solar energy conversion, although numerous studies have revealed their potentialities as catalysts for water splitting, [7][8][9][10] there have been scarce reports on POMs for CO2RR. 11,12 Besides rare examples of transition metal (M)-substituted polyoxotungstates, [13][14][15][16] reduced polyoxomolybdates (i.e.…”
Section: Introductionmentioning
confidence: 99%